2013
DOI: 10.1292/jvms.13-0265
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bovine Group A Rotavirus Using Rapid Antigen Detection Kits, RT-PCR and Next-Generation DNA Sequencing

Abstract: We investigated the sensitivity of human rotavirus rapid antigen detection (RAD) kits, RT-PCR and next-generation DNA sequencing (NGS) for detection of bovine group A rotavirus (RVA). The Dipstick ‘Eiken’ Rota (Dipstick) showed the highest sensitivity out of the seven RAD kits against all selected strains in limited dilution analyses, which was consistent with the results for equine rotavirus previously reported. RT-PCR had 100–103-fold higher sensitivity than the Dipstick. NGS using thirteen RT-PCR-negative f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Neither cytopathic effect nor the expected RT-PCR products from RNA extracted from cell culture supernatants were observed in any of the inoculated cells, indicating a lack of virus replication in these cell lines. However, using RNA-seq based strategy with DNase treatment before construction of cDNA libraries, we could obtain sufficient viral genomic sequences of RNA viruses from fecal samples not only for picornaviruses but also, in earlier studies, for other viruses such as rotavirus (Minami-Fukuda et al, 2013;Masuda et al, 2014;Nagai et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Neither cytopathic effect nor the expected RT-PCR products from RNA extracted from cell culture supernatants were observed in any of the inoculated cells, indicating a lack of virus replication in these cell lines. However, using RNA-seq based strategy with DNase treatment before construction of cDNA libraries, we could obtain sufficient viral genomic sequences of RNA viruses from fecal samples not only for picornaviruses but also, in earlier studies, for other viruses such as rotavirus (Minami-Fukuda et al, 2013;Masuda et al, 2014;Nagai et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…First, convenient genotyping of RVA was carried out using the CLC Genomics Workbench. Mapping sequence reads from five samples to VP4 and VP7 reference sequences of representative strains (Minami-Fukuda et al, 2013) revealed poor alignment with G6, G8, G10, P[1], P[5] and P[11] -the most common bovine genotypes. Near complete sequences of the 11 segments of RVA could be obtained from the resultant contigs generated by reads assembled from five samples.…”
Section: Full Genome Sequencing Of Rvamentioning
confidence: 99%
“…However, no P types were identified during the genotype detection, which is another limitation of our study. The usefulness of next-generation DNA sequencing has previously been evaluated for the direct detection of bovine rotavirus from fecal samples[ 40 ]. More meticulous rotavirus surveillance should be conducted in Yunnan, China.…”
Section: Discussionmentioning
confidence: 99%